CHANGE IN CULTURE CHANGE PRACTICE IN U.S. NURSING HOMES. (11th November 2018) - Lima, J; Schwartz, M L; Gozalo, P L; Clark, M A; Miller, S C
Abstract: We collected survey data from 1565 U.S. nursing homes (NHs) in 2009/10 and 2016/17 on three indexes aligned with NH culture change. Among NHs without high baseline scores (therefore having potential to improve), 49% improved over time in their physical score, 40% in staff empowerment, and 60% in resident-centered care. NHs in states with payment incentives for performance (p4p) at baseline were significantly more likely to improve in physical and staff empowerment scores compared to NHs in non-p4p states. NHs with higher proportions of black residents and residents with Medicaid were significantly less likely to improve in physical scores. Other NH and market characteristics were not associated with improvement. Among facilities with low index scores at Time 1, improved staff empowerment scores were associated with lower aide turnover and fewer health and quality of life deficiencies. Improved physical environment and resident scores were not significantly associated with these facility-level outcomes.